A Yup'ik dance mask from the early‐1900s connects Indigenous tradition and shorebird conservation - Liliana C. Naves (People and Nature)
Abstract A dance mask from the early 1900s reveals connections between Yup'ik people of western Alaska and shorebirds as well as their shared struggle to thrive in the modern world. As a masterpiece of Yup'ik art, the shorebird mask was embraced by the French Surrealism (musée du quai Branly‐Jacques Chirac 70.2006.41.1, Museum of the American Indian 9/3415). Nevertheless, post‐collection iconographic descriptions disagreed with bird anatomy and the species that usually occur where this mask was collected. The objectives of this study were to better understand the iconography and meaning of the shorebird mask, how this mask portrays relations between Yup'ik people and shorebirds, and its socio‐ecological context. I researched shorebird ecology and related Indigenous knowledge, Yup'ik stories and songs, the mask's original context and potential mate masks, harvest patterns and shorebird conservation history. This study clarified suitable candidate species and suggested the Yup'ik name sugg'erpak—long‐billed shorebird—to describe the mask based on Indigenous ethnotaxonomy. A geographically concentrated harvest of godwits occurs where the mask was collected. The mask relates to Agayuyaraq (way of requesting or praying for abundance), a communal ceremony whose primary purpose was to request abundant harvests, in which shamans played a central role. Yup'ik masked dances faded in the early 1900s due to suppression by Euro‐American missionaries. The creation of the sugg'erpak mask in 1905–1916 matched a period of acutely depressed shorebird populations in North America because of commercial harvest and habitat loss. The representation of sugg'erpak on a dance mask likely intended to facilitate communication with the spiritual world and request abundance, perhaps evoking or forecasting its scarcity. Shorebirds provide supplemental food, relate to key Yup'ik cultural values and are part of daily life. Animals, plants, lands and waters are not just resources, but companions to whom Yup'ik people are inherently connected and depend upon. Art and material culture embody such worldviews and relations with the natural world. Nowadays shorebird populations are again acutely depressed. Traditional Indigenous worldviews provide guidance for environmental sustainability in the modern world. Indigenous peoples are important partners in ongoing efforts for bird and shorebird conservation. Read the free Plain Language Summary for this article on the Journal blog.